OsLMP1, Encoding a Deubiquitinase, Regulates the Immune Response in Rice - Sun, Jing; Song, Wenzhong; Chang, Yuan; Wang, Yanwei; Lu, Tiegang; Zhang, Zhiguo (Frontiers in Plant Science, 2022)
Lesion mimic mutants have become an effective material for understanding plant-microbe interactions and the immune mechanism in plants. Although many mechanisms responsible for the lesion mimic phenotype have been clarified in plants, the mechanism by which lesion mimic is regulated by posttranslational modification remained largely elusive, especially in rice. In this study, a mutant with the lesion mimic phenotype was obtained and named lmp1-1. Physiological measurements and quantitative real-time PCR analysis showed that the defense response was activated in the mutants. Transcriptome analysis showed that the phenylalanine ammonia lyase (PAL) pathway was activated in the mutant, causing the accumulation of salicylic acid (SA). The results of mapping based cloning showed that OsLMP1 encodes a deubiquitinase. OsLMP1 can cleave ubiquitination precursors. Furthermore, OsLMP1 epigenetically modifies SA synthetic pathway genes by deubiquitinating H2B and regulates the immune response in rice. In summary, this study deepens our understanding of the function of OsLMP1 in the plant immune response and provides further insight into the relationship between plants and pathogenic microorganisms.